Updatist DOI-CODI: Time as a social control technology - Faria, Daniel (2023)
Among the various tools available to the DOI-CODI system for social control, time was one of the most prominent. In this article, time is understood as an instrument of social control. Time not in the abstract, chronological sense, but as a social rhythm. In the case in question, the pace imposed by the DOI-CODI system was, above all, defined by the logic of updatism, with the permanent production of information, the automatic reproduction of an entire bureaucratic and military machinery that aimed to act quickly and intensely on its targets, having, therefore, operational ramifications in the strategies and tactics of combating the internal enemy. In this sense, we also seek to discover how the instruments used by the DOI-CODI in the fight against the so-called subversion, such as and especially systematic torture, obeyed this same temporal logic. At the end of the article, we consider that even with the end of the DOI-CODI, this logic survived the end of the Cold War.